Characterization of Claypan Soils in Southeastern Kansas - M. A. Mathis II; S. E. Tucker-Kulesza; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2019)
Soil erosion reduces topsoil depth. In areas with a claypan, removal of productive topsoil reduces crop yield where the claypan layer is near the surface. The topsoil and claypan layer each have unique characteristics that impact crop production and within-field variability. To better understand these differences, the soil from an area of low crop yield and high crop yield were collected and laboratory tests were performed to determine the soil classification and undrained shear strength. Understanding the soil properties and the interaction between the topsoil and claypan layers may aid in understanding the process by which topsoil is being eroded.
Keywords: claypan soils; agriculture; soil classification; soil physical properties; undrained shear strength